Intentional awareness and its relationship to gender and specialization among university students (Journal of the College of Basic Education, 2025)
The current research aims to identify:1- Immediate intentional awareness.2- Differences in immediate intentional awareness according to the variables of gender (males, females) and specialization (scientific, humanities).The current research is limited to Al-Mustansiriya University students of both genders (males, females), and specializations (scientific, humanities) for the academic year (2023-2024) morning study, and the researchers adopted the scale of immediate intentional awareness prepared by Baer, ​​Roth, Smith, and Allen (Baer, ​​R. A., Smith G. T., & Allen, K. B. 2004)). Which consists of (39) paragraphs, The scale was translated and the psychometric properties were verified, then it was applied to a sample of (400) male and female students from the university's colleges that were selected using the random cluster method, then the data were analyzed using the Statistical Package for Social Sciences (SPSS) and the results were as follows.1- University students have immediate intentional awareness.2- There is no statistically significant difference in immediate intentional awareness according to the variables of gender (male, female) and specialization (scientific, humanities).In light of the research results, the researchers presented a number of recommendations and suggestions